2014
DOI: 10.1016/j.jaci.2014.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of abnormal lamellar body secretion and the dysfunctional skin barrier in patients with atopic dermatitis

Abstract: We review here how diverse inherited and acquired abnormalities in epidermal structural and enzymatic proteins converge to produce defective permeability barrier function and antimicrobial defense in AD. Although best known are mutations in filaggrin (FLG), mutations in other member of the fused S-100 family of proteins (i.e., hornerin [hrn] and filaggrin 2 [flg-2]); the cornified envelope precursor (e.g., SPRR3); mattrin, encoded by Tmem79, which regulates the assembly of lamellar bodies; SPINK5, which encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
197
1
20

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(232 citation statements)
references
References 133 publications
14
197
1
20
Order By: Relevance
“…Around 70% of AD cases start in children under 5 y of age, and the disease tends to show spontaneous remission with aging (16,17). Although immunological imbalances were previously proposed to explain the features of AD, such as increased immunoglobulin E (IgE) levels and the acquired immune response, recent studies showed that epidermal barrier functions critically influence the pathological features of AD (18,19). However, the cause and development of AD with respect to epidermal barrier functions have not been systematically studied.…”
mentioning
confidence: 99%
“…Around 70% of AD cases start in children under 5 y of age, and the disease tends to show spontaneous remission with aging (16,17). Although immunological imbalances were previously proposed to explain the features of AD, such as increased immunoglobulin E (IgE) levels and the acquired immune response, recent studies showed that epidermal barrier functions critically influence the pathological features of AD (18,19). However, the cause and development of AD with respect to epidermal barrier functions have not been systematically studied.…”
mentioning
confidence: 99%
“…Bu artışın da AD'deki inflamasyonun ilk sitokin kaskadını başlattığı kabul edilir. Bu durum AD FLG hastaların sağlam derilerinde proinflamatuvar bir durumun varlığını gösterir (18).…”
Section: Filagrin Gen Mutasyonlarıunclassified
“…A multiplicity of factors, including skin barrier abnormalities, defects in innate immunity response, Th2-skewed adaptive immune response, and altered skin resident microbial flora are involved in the pathogenesis of atopic dermatitis [15,16]. Whether skin inflammation is initiated by skin barrier dysfunction ("outside-in" hypothesis) or by immune dysregulation ("inside-out" hypothesis) is still in debate.…”
Section: Risk Factorsmentioning
confidence: 99%